PROSPECTS OF INTEGRATION OF NANOTECHNOLOGY TO ANTIMALARIAL HERBAL REMEDIES FOR IMPROVED THERAPEUTIC EFFICACY – A CONCISE REVIEW: Antimalarial Herbal Medicines Nanoformulations - ONYEJI, Cyprian .O. (African Journal of Traditional, Complementary and Alternative Medicines, 2022)
Background: The therapeutic utility of herbal medicinal products including antimalarial herbal remedies has been hampered by some unfavorable biopharmaceutical properties of the bioactive constituents such as low aqueous solubility, poor oral bioavailability, poor intestinal permeability and large molecular size. Al these biopharmaceutical issues are responsible for observed reduced in vivo efficacy of some herbal products compared to their in vitro efficacy. These drawbacks can by countered by the integration of nanotechnology. The present article identified the various documented nanosystems and examined the recent efforts in the deployment of nanotechnology in formulations of antimalarial herbal medicines for improved therapeutic efficacies. Also safety considerations in clinical applications of nanoformulations were highlighted. Methods: The information was acquired from an extensive literature searching of electronic databases such as Science-Direct, PubMed, and Google-Scholar to obtain appropriate articles made in the English language which were published up to 2022, using a combination of relevant keywords. Results: Only very few herbal antimalarial remedies such as extracts of Azadirachta indica, Momordica charantia, Curcuma longa, and Artemisia species have been nanoformulated and evaluated for antimalarial efficacy. In all these studies, the drug-loaded nanoformulations exhibited significantly higher in vitro and/or in vivo antimalarial efficacy. The different nanoformulations of antimalarial herbal remedies that have been reported include nanoparticles of lipid-based, cyclodextrin, chitosan/lecithin , liposomes, nanosuspension, nanoemulsions, and metal-based nanoparticles.. Conclusion: Different types of nanoformulations of herbal antimalarial drugs have been reportedly prepared by different techniques and these offer advantages of improved efficacies. Safety concerns present a hurdle to clinical applications.